Analisis Kualitas Layanan terhadap Kepuasan Konsumen di Toko Genesis Baru Condongcatur Yogyakarta - wedu, selvianus; Uswatun Chasanah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effect of service quality on customer satisfaction at Toko Genesis Baru, Condongcatur, Yogyakarta. Service quality is measured using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This research employs a quantitative approach with data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using multiple linear regression, including t-tests (partial), F-test (simultaneous), and coefficient of determination (R²). The descriptive analysis indicates that service quality is categorized as fairly good to good, while the level of customer satisfaction is considered high. Partially, the dimensions of reliability and responsiveness have a positive and significant effect on customer satisfaction. In contrast, tangibles, assurance, and empathy do not show a significant effect. Simultaneously, service quality has a significant effect on customer satisfaction. The coefficient of determination (R²) of 0.493 indicates that service quality explains 49.3% of the variance in customer satisfaction, while the remaining 50.7% is influenced by other factors outside the research model. These findings suggest that customers prioritize reliability and responsiveness in evaluating their satisfaction. Therefore, management should focus on improving these dimensions to enhance overall customer satisfaction.